Creationism as a misconception: socio-cognitive conflict in the teaching of evolution - Foster, Colin (Taylor and Francis Group, 2012)
This position paper argues that students' understanding and acceptance of evolution may be supported, rather than hindered, by classroom discussion of creationism. Parallels are drawn between creationism and other scientific misconceptions, both of the scientific community in the past and of students in the present. Science teachers frequently handle their students' misconceptions as they arise by offering appropriate socio-cognitive conflict, which highlights reasons to disbelieve one idea and to believe another. It is argued that this way of working, rather than outlawing discussion, is more scientific and more honest. Scientific truth does not win the day by attempting to deny its opponents a voice but by engaging them with evidence. Teachers can be confident that evolution has nothing to fear from a free and frank discussion in which claims can be rebutted with evidence. Such an approach is accessible to children of all ages and is ultimately more likely to drive out pre-scientific superstitions. It also models the scientific process more authentically and develops students' ability to think critically.